Severe Disabling Myalgia as an Initial Presentation of Polyarteritis Nodosa. (7th April 2019) - Senarathna, H. M.; Fonseka, C. L.; Perera, H. A. S.; De Silva, P. U. T.; Weerarathna, T. P.
Abstract : Background . Polyarteritis nodosa (PAN) is a form of necrotizing vasculitis affecting medium or small blood vessels with multiorgan involvement. Although myalgia is a clinical feature of PAN, severe disabling myalgia as the initial presentation is rarely noted. Case Presentation . We present a case of 54-year-old male with recently detected chronic kidney disease admitted with progressive severe disabling muscular pains predominantly over calves with constitutional symptoms for seven weeks. He was weak to mobilize out of the bed. Later, he developed a vasculitic rash, unilateral ulnar claw, and bilateral foot drop. His skin and muscle biopsies showed evidence of vasculitis. His renal and mesenteric artery CT angiogram revealed stenosed segment of the celiac artery without evidence of visible aneurysms elsewhere. He completed six cycles of intravenous cyclophosphamide pulse therapy with high-dose oral prednisolone with good response. With continuation of aggressive immunosuppression and rehabilitation for five months, the patient improved and was able to walk without support. Conclusion . Musculoskeletal predominant PAN, even though rare, needs to be considered in patients presenting with disabling muscle pain and weakness. These features may herald over days to months along with constitutional symptoms before other systems getting affected. Early recognition of such symptoms and initiating specific treatment would be important for better outcomes.